Keefektifan Model Discovery Learning terhadap Hasil Belajar Siswa pada Materi Larutan Penyangga - Agustina, Diah Tria; Cahyono, Edy; Widiarti, Nuni (Chemistry in Education, 2019)
This study aims to determine the effectiveness of discovery learning model to students’ learning outcomes in SMA Negeri 1 Sokaraja on buffer solution material. This research was true-experiment consisting of preliminary stage, preparation stage, implementation stage, and final stage. The applied design was experiment control group posttest-only design. Population in this research was class XI MIPA SMA Negeri 1 Sokaraja. Sampling was done using cluster random sampling technique. Class XI MIPA 5 as experiment class and class XI MIPA 6 as control class. Data collection includes documentation, tests, observations, and questionnaires. The result of the research shows that learning with discovery learning model in the experimental class reaches 91.18% (31 of 34 students), 100% practicum skills, 100% student attitude profile. While in the control class using ordinary learning (lecture and practice) obtained learning mastery of 67.65% (23 of 34 students), skills proficiency profile of 97%, and attitudinal profile of 94%. The experimental class students gave a positive response that the application of discovery learning model can increase students' interest and motivation. Based on the results of this study, it can be concluded that discovery learning model effective to students' learning outcomes in SMA Negeri 1 Sokaraja on buffer solution material.